2021
DOI: 10.1136/bmjopen-2021-051735
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and preferences of palliative and end-of-life care among patients with cancer in mainland China: a cross-sectional study

Abstract: ObjectivesThis study aimed to investigate the knowledge and attitudes of patients with cancer of palliative care and their preferences regarding end-of-life care in mainland China.DesignA cross-sectional study.SettingThis study was conducted in a tertiary cancer hospital.ParticipantsTwo hundred forty-seven patients with cancer were recruited and consented to fill out the questionnaires.Outcome measuresThe participants’ knowledge and attitudes of palliative care and their preferences of end-of-life care involvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Simultaneously, medical staffs don’t fully understand the patients’ intention to participate in EOLD due to inadequate communication with patients [ 27 ]. All of these may result in patients in China mainland to have little opportunity to understand EOLD related knowledge and to participate in discussion on EOLD, which has been confirmed in recent studies from China mainland [ 14 16 ]. More importantly, the true willingness of patients in China mainland to participate in EOLD discussions remains elusive.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Simultaneously, medical staffs don’t fully understand the patients’ intention to participate in EOLD due to inadequate communication with patients [ 27 ]. All of these may result in patients in China mainland to have little opportunity to understand EOLD related knowledge and to participate in discussion on EOLD, which has been confirmed in recent studies from China mainland [ 14 16 ]. More importantly, the true willingness of patients in China mainland to participate in EOLD discussions remains elusive.…”
Section: Discussionmentioning
confidence: 97%
“…On the contrary, very few patients with cancer (2.8 to 18.8%) participated in the process of EOLD in China mainland [ 14 , 15 ]. Such heavily contrast may be attributed to policy and cultural differences between Western countries and China mainland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hospice care in China is relatively nascent compared to some Western countries (e.g., United States, Canada, England, Australia), yet growing steadily [ 12 , 13 , 14 ]. Since hospice care was introduced in 1988 [ 15 ], it has made great progress, and by 2017, there were 2343 medical institutions with hospice care departments in China [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent study with community residents in Hangzhou, China, found that only 50.3% of adult populations aged 40 and above in China were aware of hospice care [ 28 ], as compared to 86% and 76% of the general population in the United States [ 33 ] and Northern Ireland [ 34 ], respectively. Awareness of hospice care is even lower among cancer patients (5.8%) [ 14 ] and oncologists in China [ 35 ]. Hospice care is often perceived as appropriate only for those facing imminent death in China.…”
Section: Introductionmentioning
confidence: 99%